2014
DOI: 10.4238/2014.october.27.16
|View full text |Cite
|
Sign up to set email alerts
|

Association between polymorphisms in the thymidylate synthase gene and risk of breast cancer in a Mexican population

Abstract: ABSTRACT. Breast cancer (BC) is the leading cause of cancer-related deaths among women in Mexico. Two single-nucleotide polymorphisms (SNPs) in the thymidylate synthase (TS) gene, the 28-base pair (bp) 8750©FUNPEC-RP www.funpecrp.com.br Genetics and Molecular Research 13 (4): 8749-8756 (2014) A. Quintero-Ramos et al. tandem repeat in the TS 5'-untranslated enhanced region (TSER) and the 6-bp insertion/deletion in the TS 3'-untranslated region (TS 3'-UTR), increase the rate of misincorporation of uridylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
1
9
1
Order By: Relevance
“…Our results are very similar to those reported for the Spanish [27] and Mexican [28] women. The studies on other populations have found the significant associations between the TYMS gene TSER variations and breast cancer development [14].…”
Section: Resultssupporting
confidence: 91%
“…Our results are very similar to those reported for the Spanish [27] and Mexican [28] women. The studies on other populations have found the significant associations between the TYMS gene TSER variations and breast cancer development [14].…”
Section: Resultssupporting
confidence: 91%
“…As a multitargeted antifolate, pemetrexed inhibits several de novo synthesis enzymes for purine and pyrimidine, including TYMS. Previous clinical and in vitro studies showed that cancer cell lines with TYMS expression showed poor sensitivity to cisplatin-and taxane-based chemotherapy regimens (24,25). Pemetrexed treatment in non-small cell lung cancer patients indicated that low TYMS mRNA expression was associated with increased ORR (26), and TYMS was an appropriate biomarker for pemetrexed chemotherapy response in non-small cell lung cancer (9,10,27).…”
Section: Tyms Expression --------------------------------------------mentioning
confidence: 99%
“…Genes or pathways studied have included those related to hormone metabolism, hormone receptors, and hormone coactivators or supressors, 148,164–169 growth factors, 149,170176 matrix metalloproteinases, 177,178 inflammation and energy balance, 158,179184 metabolism of xenobiotic compounds and oxidative stress, 159,185188 DNA repair, 160,161,163,189 and angiogenesis. 190 Results reported in these publications should be interpreted with caution, given that approximately 60% of the candidate gene analyses included in our report did not adjust for genetic ancestry, which is a known confounder in genetic association studies in admixed populations.…”
Section: Common Genetic Polymorphisms and Risk Of Breast Cancermentioning
confidence: 99%